The impact of subsidies in a transboundary pollution game with myopic players. (September 2021) - Li, Liming; Chen, Weidong
Highlights: The quantitative relationship between subsidies and emission reductions in the transboundary pollution game model is built. The impact of myopic on the equilibrium solution of the game is studied. The critical condition for a farsighted developing country to turn into a myopic developing country is founded. An example is given to show the effectiveness of the obtained results. Abstract: In this paper, we study the impact of green subsidies in an international transboundary pollution game. In the game, the developed country only suffers from paying the subsidy but does not reduce emissions, while developing countries reduce their emissions after receive the subsidy. Furthermore, we assume that developing countries can be myopic, which means that they choose their reduction policy without taking into account the future levels of pollution. The results show that when some of the developing countries are myopic, the optimal reduction policy is much lower than that in the case where all of the developing countries are farsighted. The level of pollution is much higher for the former case than the latter one. However, for developed countries, the presence of a certain number of myopic developing countries can maximize their payoffs. Finally, we find the critical condition for a farsighted developing country to adopt a myopic framework. The findings of this paper could offer valuable guidances for climate policy makers.